Rice bran extract improves mitochondrial dysfunction in brains of aged NMRI mice. (2nd January 2016) - Hagl, Stephanie; Berressem, Dirk; Grewal, Rehka; Sus, Nadine; Frank, Jan; Eckert, Gunter P.
Abstract : Objectives: Aging represents a major risk factor for neurodegenerative diseases such as Alzheimer's disease. Mitochondria are significantly involved in both the aging process and neurodegeneration. One strategy to protect the brain and to prevent neurodegeneration is a healthy lifestyle including a diet rich in antioxidants and polyphenols. Rice bran extract (RBE) contains various antioxidants including natural vitamin E forms (tocopherols and tocotrienols) and gamma-oryzanol. In this work, we examined the effects of a stabilized RBE on mitochondrial function in 18-month-old Naval Medical Research Institute mice (340 mg/kg body weight/day), which received the extract for 3 weeks via oral gavage. Methods: Mitochondrial parameters were measured using high-resolution respirometry (Oroboros Oxygraph-2k), Western blot analysis, and photometric methods in dissociated brain cells, isolated mitochondria, and brain homogenate. Vitamin E concentrations in blood plasma and brain tissue were measured using HPLC with fluorescence detection. Results: Aging leads to decreased mitochondrial function (decreased mitochondrial respiration and ATP production) and decreased protein expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1alpha). RBE administration increased alpha-tocopherol concentrations in the brain and compensated for age-related mitochondrial dysfunction by increasing mitochondrial respiration, membrane potential, PGC1alpha protein expression, and citrate synthase activity. Furthermore, resistance of brain cells to sodium nitroprusside-induced nitrosative stress was improved. Discussion: According to these results, RBE is a promising candidate nutraceutical for the prevention of age-related neurodegenerative diseases.